Identification, typing, ecology and epidemiology of coagulase negative staphylococci associated with ruminants. Issue 1 (January 2015) - Vanderhaeghen, Wannes; Piepers, Sofie; Leroy, Frédéric; Van Coillie, Els; Haesebrouck, Freddy; De Vliegher, Sarne
Highlights Various molecular methods for identification and typing of ruminant coagulase negative staphylococci (CNS) are now available. Five CNS species cause the majority of CNS intramammary infections (IMI) in cows. In an ecological framework, some CNS species can be environmental and others host-adapted. In an epidemiological framework, some CNS IMI can be contagious and others opportunistic. Much is yet to be learned about the ecology and epidemiology of the different CNS species causing IMI in ruminants.